Stigma and suicide risk among the LGBTQ population: Are anxiety and depression to blame and can connectedness to the LGBTQ community help?. Issue 2 (3rd April 2019) - Kaniuka, Andrea; Pugh, Kelley C.; Jordan, Megan; Brooks, Byron; Dodd, Julia; Mann, Abbey K.; Williams, Stacey L.; Hirsch, Jameson K.
Abstract: LGBTQ individuals may be at risk for suicidal behavior due to perceived stigma and psychopathology. However, protective factors, such as community connectedness, may reduce risk. We examined depression and anxiety as mediators of the linkage between perceived stigma and suicidal behavior, and the moderating role of LGBTQ community connectedness. Among our sample of LGBTQ persons ( N  = 496), psychopathology mediated the association between perceived stigma and suicidal behavior. Connectedness moderated the relation between perceived stigma and depression, and between perceived stigma and suicidal behavior in the anxiety model. Therapeutically addressing stigma and promoting LGBTQ community connectedness may reduce risk for suicidal behavior.